2015
DOI: 10.1249/mss.0000000000000704
|View full text |Cite
|
Sign up to set email alerts
|

Using GPS, GIS, and Accelerometer Data to Predict Transportation Modes

Abstract: This study uses real-life data from a large sample set to test a method for predicting transportation modes at the trip level, thereby providing a useful complement to time unit-level prediction methods. By enabling predictions on the basis of a limited number of observations, this method may decrease the workload for participants/researchers and provide relevant trip-level data to investigate relations between transportation and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 35 publications
3
39
0
Order By: Relevance
“…Previous studies indicated that utilizing GPS devices is a practical method to accurately estimate humans' locomotion speed [26][27][28][29][30]. While adding GPS data (i.e., speed) to accelerometer data increases transport mode detection performance when differentiating between active and passive modes of transport [24,[31][32][33], these studies rarely included different types of walking or cycling activities or different sub-types of the stationary class such as sitting, standing and lying. Although studies have included GPS speed to improve PA type detection for more fine-grained activities [5,13,34], they have a number of limitations that still have to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that utilizing GPS devices is a practical method to accurately estimate humans' locomotion speed [26][27][28][29][30]. While adding GPS data (i.e., speed) to accelerometer data increases transport mode detection performance when differentiating between active and passive modes of transport [24,[31][32][33], these studies rarely included different types of walking or cycling activities or different sub-types of the stationary class such as sitting, standing and lying. Although studies have included GPS speed to improve PA type detection for more fine-grained activities [5,13,34], they have a number of limitations that still have to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…As an empirical illustration, the present study relied on GPS tracking and on a mobility survey to precisely assess places visited over 7 days. 8,13,14 The resulting ability to disentangle truly residential from nonresidential effects allowed us to demonstrate the existence of a major generator of confounding that we refer to as the "residential" effect fallacy (we use quotes to put into question the residential nature of the underlying effect), quantify its magnitude, and correct for it. As an illustration, we focus on the well-known hypothesis that the residential accessibility to services fosters transport walking.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have relied on accelerometers to derive objective measures of physical activity (12,13). However, studies were less successful in linking transport behavior with physical activity because identifying trips with their exact start and end times is required to perform this linkage (5,14,15). Unfortunately, study designs including trip recognition and accelerometer data collection often result in datasets with very precise measures but with limited sample sizes.…”
Section: Introductionmentioning
confidence: 99%